Psychological status and well being among Emergency Department nurses in Hospitals in Malaysia - Thiruchelvam, Dashant (2017)
Objective: To determine the psychological status, particularly the level of depression, anxiety and stress level among Emergency Department (ED) nurses in hospitals in Malaysia and its association to demographic factors. Methods: A survey research was conducted in the ED of seven hospitals in Malaysia. A total of 168 nurses from the ED who fulfilled the inclusion criteria were included in the study. Each nurse was given a set of questionnaire consisting demographic background and the DASS 21 for data collection. Results: The results from 168 nurses showed a total of 23 nurses (14.3%) recorded scores for moderate depression, 1 nurse (0.6%) recorded a score for severe depression and another 1 nurse (0.6%) recorded a score for extremely severe depression respectively. A total of 36 nurses (21.4%) recorded moderate anxiety, with 8 nurses (4.8%) recorded severe anxiety and 5 nurses (3%) recorded extremely severe anxiety. Stress levels score showed 2 nurses (1.2%) recorded moderate stress levels and none was recorded for severe – extremely severe stress. Among the demographic factors tested, gender was a significant factor associated with depression (β = 6.134, p = 0.031) and anxiety (β = 6.780, p = 0.015) respectively. Conclusion: The psychological status, particularly depression, anxiety and stress level among ED nurses were generally low. The depression and anxiety level was noted to be more affected by demographic factors compared to stress level.